ANALISIS POTENSI EKOWISATA DANAU LIMBOTO (PENDEKATAN ANALISIS SWOT) - Sri Sunarti; Desrika Talib (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2020)
The purpose of this research is to reveal the ecotourism potential of Limboto lake as natural tourism which needs to be improved and developed. The research method used is the SWOT analysis method with descriptive qualitative research type. The results of the research show that; Strengths include the cultural diversity of the local community which has been preserved until now, the extraordinary tourism potential of Lake Limboto and apart from being a tourist attraction, this location is a place of livelihood for people who work as fishermen. Weakness among others are, the absence of a clear strategy in the development of Lake Limboto and inadequate facilities and infrastructure. Opportunity, among others, support from various parties, especially the government, although it is still limited to a plan that cannot be realized. There have been efforts to form a community that cares about tourism, and is close to other tourism objects. Threats, among others, are tourism development in this area is not yet a top priority and also a lack of public awareness in preserving Lake Limboto tourism objects.